Name Disambiguation Analysis Using the Word Sense Disambiguation Method in Hadith - Prasetio, Ageng; Bijaksana, Mochammad Arif; Suryani, Arie Ardiyanti (Universitas Hamzanwadi, 2020)
Name disambiguation is the problem solving process to find similar names in sentences. The ambiguity of names can be found in hadith of Sahih Bukhari, names